Diverse Spectrum of Presentation of Coronary Slow Flow Phenomenon: A Concise Review of the Literature - Muhammad A. Chaudhry; Marcus Smith; Elias B. Hanna; Ralph Lazzara (Cardiology Research and Practice)
The coronary slow flow phenomenon (CSFP) is a disease entity characterized by slow progression of angiographic contrast in the coronary arteries in the absence of stenosis in the epicardial vessels. CSFP has a diverse presentation from mild chest discomfort to ST-segment elevation myocardial infarction. It can also have severe morbidity and mortality implications and can significantly hamper the quality of life of those affected. In this paper we present two patients with CSFP highlighting the diverse spectrum of presentation. A concise review of the literature is also provided emphasizing the epidemiology, pathogenesis, diagnostic parameters, treatment modalities, and clinical significance of this phenomenon.